El desarrollo humano en Colombia (2007)
The Human Development, according to the international law, is a right and a necessary condition forthe human rights. The most evident relation appears with the Economic, Social and Cultural HumanRights (Eschr), especially with the principle of non-return, which implies that the Development may bedemanded by the citizens, because it is the guarantee of a non-backward movement in the advances ofprotection of the Eschr. In any case, the definition of Development as a right depends on the normative order of each State. In Colombia, the Human Development appears in the Constitution, in multiplearticles, from which it is possible to construct, along with the jurisprudence of the Constitutional Court, aconcept that, does not adjust to the perspective of the international soft law, although it raises someindispensable obligations to the State. In spite of it, and although the structure of the State about theplanning and execution of the development models is quite efficient, at least in the writing of the norms,the lack of an effective control in order to get the profits of the development, and the difficulty to definea legal resource that allows the citizens to demand the fairness as far as the benefits of the development,do not make possible to consider the existence of a Right to Development in Colombia today.